Sexual dimorphism in the genus Acothrura Melichar, 1915 (Hemiptera: Lophopidae) and description of male and female specimens of A. impunctata (Jacobi, 1905) - Liu, Yidi; Ren, Yujie; Wang, Menglin (Zootaxa, 2024)
The sexual dimorphism of Acothrura impunctata (Jacobi, 1905) is confirmed by molecular analysis. Its male morphological characteristics are firstly reported. A key to species of Acothrura is provided.